Participatory and Equitable Climate Risk Mapping and Adaptation Planning: What is it? Why it matters? How to do it? - Gartaula, Hom; Raviz, Jeny; Hellin, Jon; Laborte, Alice; Bacud, Susan; Datoon, Rodmyr; Eschavez, Chona; Fabillar, Jennifer; Gonsalves, Julian; Rosimo, Magnolia (International Rice Research Institute, 2025)
As climate change intensifies in the Philippines, local adaptation planning has become essential for protecting vulnerable farming communities. This video, produced by IRRI and its partners, showcases the Climate-Smart Mapping and Adaptation Planning (CS-MAP) approach implemented in Quezon and Batangas, Philippines. It emphasizes a locally-led, participatory methodology that integrates climate risk mapping with a social equity lens, actively involving diverse community members in planning adaptation strategies. The project highlights the importance of recognizing community heterogeneity and targeting both geographic and social vulnerabilities. Through collaborative mapping with stakeholders, local governments and organizations develop context-specific climate adaptation plans that center marginalized voices, fostering ownership, inclusivity, and sustainable climate resilience, which can be used by the local government units (LGUs).